Migration patterns and spatial connectivity of Pallas's Gulls (Ichthyaetus ichthyaetus) from Alakol lake, Kazakhstan using ring recovery and tracking data - Viktoriya O. Ilina; Bekzhan T. Berdikulov; Fumin Lei; Aleksandr N. Filimonov; Yekaterina E. Akentyeva; Gang Song; Aizhan E. Tashimova; Andrey E. Gavrilov (Avian Research, 2025)
Understanding migration patterns and spatial connectivity is crucial for conserving long-distance migratory birds. While satellite telemetry has advanced the study of large gulls, Pallas's Gull (Ichthyaetus ichthyaetus) remains relatively understudied, with limited data on its migration routes and habitat use, particularly in Central Asia. This study integrates 684 ring recoveries (1968–2024) and GPS tracking data to analyze the migration ecology of individuals breeding at Alakol Lake, Kazakhstan. Ring recoveries confirm migratory connectivity across Kazakhstan, Russia, Uzbekistan, Turkmenistan, Iran, and Pakistan, with wintering records as far as India, Kuwait, Bangladesh, and Ethiopia. GPS tracking of a single individual (June 2020–August 2021) revealed a migration route from Alakol Lake to the Arabian Sea, with key stopovers at Zaisan Lake, Balkhash Lake, the Aral Sea, Aydar Lake, and the Amu Darya River. Notably, a post-breeding northward dispersal to Zaisan Lake and southern Russia was identified before the southward migration commenced. These findings highlight the significance of Kazakhstan's lakes as breeding and migratory hubs and the need to protect critical stopover sites in Central Asia. Given increasing anthropogenic pressures on wetland habitats, this research provides essential baseline data for conservation planning and enhances the broader understanding of gull migration ecology.